Thermal degradation and fire resistance of unsaturated polyester, modified acrylic resins and their composites with natural fibres - Manfredi, Liliana Beatriz (2006)
The thermal degradation and fire resistance of different natural fibre composites were studied. Unsaturated polyester (UP) and modified acrylic resins (Modar) were used as matrix composites. The smoke emission of the materials was also analysed, as well as, the performance against the fire of the biocomposites and glass reinforced composites was compared. Thermal degradation indicated that the Modar matrix composites were more resistant to temperature than the composites with UP matrix. Flax fibre, due to their low lignin content, exhibit the best thermal resistance among the natural fibres studied. From the results obtained about the thermal and fire resistance of the composites it is possible to conclude that the flax fibre seems to be the most adequate to be used, due to the long time to ignition and the long period prior to reach the flashover. On the other hand, the jute fibre composites showed a short duration but a quick growing fire with the lowest smoke emission. The low smoke is an important advantage, which reduces one of the main hazards of fire.